Schrödinger’s cheetah. (Economist, 2019)
The article discusses the rise of quantum computing. Researchers at the U.S. information technology company Google have developed a quantum computer. Computer programmers are recognized for their ability to create algorithms that exploit the quantum capabilities of computers. Quantum computers use three counterintuitive phenomena, including superposition, entanglement and amplitudes.